Cellular microenvironment: a key for tuning mesenchymal stem cell senescence - Sun, Wenyang; Lv, Jiacheng; Guo, Shu; Lv, Mengzhu (Frontiers in Cell and Developmental Biology, 2023)
Mesenchymal stem cells (MSCs) possess the ability to self-renew and differentiate into multiple cell types, making them highly suitable for use as seed cells in tissue engineering. These can be derived from various sources and have been found to play crucial roles in several physiological processes, such as tissue repair, immune regulation, and intercellular communication. However, the limited capacity for cell proliferation and the secretion of senescence-associated secreted phenotypes (SASPs) pose challenges for the clinical application of MSCs. In this review, we provide a comprehensive summary of the senescence characteristics of MSCs and examine the different features of cellular microenvironments studied thus far. Additionally, we discuss the mechanisms by which cellular microenvironments regulate the senescence process of MSCs, offering insights into preserving their functionality and enhancing their effectiveness.